An adult patient with common B-cell acute lymphoblastic leukaemia who presented with pancreatic involvement, description of the second adult case and review of paediatric cases. (22nd May 2014) - Pamuk, Gulsum Emel; Tapan, Umit; Aksoy, Sema; Umit, Hasan
Abstract : Pancreatic involvement in acute lymphoblastic leukaemia (ALL) may go unrecognised. There are only a few paediatric cases; nevertheless, presentation with pancreatic involvement in an adult patient with ALL has been reported rarely. Our 52-year-old male patient came to us with abdominal pain, nausea and vomiting; he had pancreatic enlargement on CT. He was diagnosed with common B-cell ALL with pancreatic involvement. The patient obtained haematological remission and the pancreatic enlargement regressed after chemotherapy, but later he had central nervous system and liver relapses. He died 6 months after diagnosis because of progressive pneumonia and chemotherapy-resistant ALL with multiple extramedullary relapses.